2018
DOI: 10.1101/266882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SETD3 protein is the actin-specific histidineN-methyltransferase

Abstract: Protein methylation is one of the most common post-translation modification (PTM) in eukaryotic cells [for review see Clarke, 2013] and histones are probably the best studied substrates of protein Nmethyltransferases. Much is therefore known about methylation of lysine and arginine residues in histones as well as the fundamental role of such modifications in the epigenetic control of mammalian gene expression [Greer and Shi, 2012]. However, an increasing number of studies show methylation of non-histone prote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Mammalian actin can be isolated with one of seven different modifications at the N -terminus, which are mediated by a combination of aminopeptidases, NAA80 acetyl transferase (Drazic et al, 2018; Goris et al, 2018), and ATE1 arginyl-tRNA-protein transferase (Karakozova et al, 2006). Furthermore, human actin is methylated on His-73 by the SETD3 methyl transferase (Kwiatkowski et al, 2018; Wilkinson et al, 2018). A. thaliana actin is N -terminally acetylated at alanine and is only weakly (9%) methylated on His-74, equivalent to mammalian and yeast His-73 (Wilkinson et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mammalian actin can be isolated with one of seven different modifications at the N -terminus, which are mediated by a combination of aminopeptidases, NAA80 acetyl transferase (Drazic et al, 2018; Goris et al, 2018), and ATE1 arginyl-tRNA-protein transferase (Karakozova et al, 2006). Furthermore, human actin is methylated on His-73 by the SETD3 methyl transferase (Kwiatkowski et al, 2018; Wilkinson et al, 2018). A. thaliana actin is N -terminally acetylated at alanine and is only weakly (9%) methylated on His-74, equivalent to mammalian and yeast His-73 (Wilkinson et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We next established a system to prepare His-73-methylated human β and γ actin. Recent work has shown that the mammalian SETD3 methyl-transferase methylates His-73 of human actins, using S -adenosyl methionine as a methyl group donor (Kwiatkowski et al, 2018; Wilkinson et al, 2018; Figure 3A). To promote actin His-73 methylation, we co-expressed the mammalian SETD3 and β or γ actin in P.pastoris cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research in this area is difficult due to the lack of effective reagents for probing protein-histidine methylation (Ning et al, 2016). Recently, SET domain containing 3 (SETD3), which was previously shown to act as a histone lysine methyltransferase, was identified as an actin histidine methyltransferase, functioning to control replication and pathogenesis in multiple mouse models for enterovirus infection as well as the regulation of smooth muscle contractility linked to primary dystocia (Diep et al, 2019; Kwiatkowski et al, 2018; Wilkinson et al, 2019). In contrast, however, the biological function and molecular characterization of METTL18 have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…SETD6 methylates p65 (RelA) (24,28), and other non-histone proteins (29)(30)(31). SETD3 was initially reported to methylate histones (32,33), but recently found to a histidine residue in b-actin (25,26,34). However, little is known about the function of mammalian SETD4.…”
Section: Introductionmentioning
confidence: 99%